2008
DOI: 10.1097/01.tp.0000331449.77826.70
|View full text |Cite
|
Sign up to set email alerts
|

Functional Capacity of Human Islets Shipped Long Distances

Abstract: Up to 60% of patients (pts) undergoing LDLT develop biliary complications, most within the fi rst 3 months postoperatively (PO). We describe a change in anastomotic technique that signifi cantly decreased the incidence of biliary complications at our center. This retrospective is a longitudinal cohort analysis of 77 LDLT completed at our institution since 2001. For the fi rst 59 LDLT, the biliary anastomosis, either duct-to-duct (49) or Roux-en-Y (10) reconstruction, were completed with a running absorbable su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…We have made microcapsules of barium alginate and shown that insulin-producing porcine cells can function as efficiently inside such capsules as when nonencapsulated (2). Moreover, human islets placed in these capsules normalize blood glucose levels when engrafted in diabetic mice (3,4). In the current study, we transplanted four type 1 diabetic humans with encapsulated human islets.…”
mentioning
confidence: 99%
“…We have made microcapsules of barium alginate and shown that insulin-producing porcine cells can function as efficiently inside such capsules as when nonencapsulated (2). Moreover, human islets placed in these capsules normalize blood glucose levels when engrafted in diabetic mice (3,4). In the current study, we transplanted four type 1 diabetic humans with encapsulated human islets.…”
mentioning
confidence: 99%
“…The high cost of human islet isolation and the requirements for a highly skilled islet isolation team with specialized equipment limit the number of centers that can perform consistent and successful human islet isolations 1 . As such, human islet research has commonly relied on the shipment of islets from expert centers, such as those affiliated with the Integrated Islet Distribution Program (IIDP) [3][4][5] . To date, the IIDP has distributed over 261 million human islets to approximately 400 independent researchers across the globe, both in academia and industry.…”
Section: Introductionmentioning
confidence: 99%
“…One factor that has not been extensively studied is the optimal length of time that human islets should be held in culture prior to shipping to achieve the best islet recovery upon receipt. Some investigators have requested that IIDP islets be shipped out immediately after isolation; however, culturing the islets prior to shipment has been a standing practice of isolation centers to hopefully descrease loss of islet equivalents (IEQ) during shipment 5,14 .…”
Section: Introductionmentioning
confidence: 99%